GW24-e2122 Pentraxin-3 predicts 1-year major adverse cardiovascular events after coronary stent implantation. (1st October 2013) - HaiBo, Liu; Chunming, Wang; Wangjun, Yu; Limei, Zhang; Yong, Cao; Yu, Fang; Yingchun, Bao; Junbo, Ge
Abstract : Objectives: Coronary stent implantation induces a significant inflammatory reaction in the injured vessel wall that leads to the adverse cardiovascular events. A long pentraxin, PTX3, is a useful marker for localised vascular inflammation and damage to the cardiovascular system, however, its prognostic value in patients after coronary stent implantationremains unclear. The aim of this study was to assess the prognostic value of PTX3 in patients with coronary artery disease after coronary stent implantation. Methods: 164 consecutive patients with coronary artery disease and undergoing coronary stenting were prospectively enrolled for clinical 1-year follow-up. Plasma PTX3 levels were determined in the second morning after coronary stent implantation. The major adverse cardiac events, which were defined as cardiac death, repeat revascularisation and rehospitalisation for worsening heart failure, were monitored for 1 year after admission. Results: During the 1-year follow-up period, there were 39 cardiac events, including 6 cardiac deaths, 17 repeat revascularisation and 16 rehospitalisation for worsening heart failure. In a stepwise Cox regression analysis including 13 well-known clinical and biochemical predictors of CAD outcome, PTX3 (relative risk 3.108 per 10-fold increment, P < 0.01), cTnI (relative risk 1.914 per 10-fold increment, P < 0.01) and multiple stents (relative risk 2.025 yes = 1, P = 0.027) but not hsCRP, were independently associated with the 1-year cardiac events. The plasma levels of PTX3 were higher in patients with cardiac events than those without (5.34 ± 0.79 ng/mL vs. 4.10 ± 0.81 ng/mL, P < 0.01). The cardiac event rate was higher in patients with increased PTX3 (>4.39 ng/mL of median value) than those without (35.4% vs. 12.2%, P < 0.01). A Kaplan–Meier analysis revealed that patients with increased PTX3 had a higher risk for cardiac events than those without ( P < 0.01) Conclusions: PTX3, cTnI and multiple stents may be potent and independent predictors for 1-year cardiac events in patients after coronary stent implantation. Measurement of plasma PTX3 may substantially improve the early risk stratification of patients undergoing coronary stenting.